Strategic Decision Making and Problem Solving Case Studies at Indonesian Petroleum and Exploration Companies - Febrian Hermawan; Agus Tamrin Reni; Della Jane Wijaya; Verina Verina; Wahyu Satriyo Wicaksono; Agustinus Setyawan (Jurnal Ilmu Sosial Mamangan, 2022)
This study aims to analyze issues that become problems related to company performance and how the process of making strategic decisions on these problems, especially in the oil and natural gas sector companies. The research uses an Australian unit oil and gas company which currently has a project in Indonesia, specifically in Batam City. Methods of data collection were obtained through interviews and brainstorming with corporate leaders and project teams from the sample company. The root causes of the company's problems are analyzed through a SWOT analysis, then the problem risk analysis is sorted based on priority scale. The results of the analysis found that there are six main problems that are often found in companies and can affect corporate performance. The accuracy of project completion is a problem with the highest level of risk. Accidents and design engineering have a high risk, while human resource management, raw material supply, and alternative energy have a moderate risk.